1991
DOI: 10.1063/1.106173
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous behavior of ion-implanted GaSb

Abstract: Anomalous elevations up to 6 μm of the ion-implanted GaSb surface were observed. This swelling phenomenon is related to the formation of a porous layer and is dependent on the mass, energy, and dose of the implanted ions. A strong amount of oxygen was measured in the porous layers but this oxygen is likely not responsible for the swelling. The behavior of implanted GaSb is very similar to that of InSb previously described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 14 publications
3
29
2
Order By: Relevance
“…In the case of GaN, [5][6][7][8] nitrogen bubbles and gallium nanocrystals are formed in the amorphized layer by ion irradiation. In the case of GaSb [9][10][11][12][13][14][15][16][17] and InSb, 9,17,18) unusual behaviors, such as elevation, swelling, and the formation of holes, voids, nanofibers, and cellular structures with nano to submicron dimensions, are observed on irradiated surfaces. Similar phenomena occur in irradiated Ge surfaces (for example, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of GaN, [5][6][7][8] nitrogen bubbles and gallium nanocrystals are formed in the amorphized layer by ion irradiation. In the case of GaSb [9][10][11][12][13][14][15][16][17] and InSb, 9,17,18) unusual behaviors, such as elevation, swelling, and the formation of holes, voids, nanofibers, and cellular structures with nano to submicron dimensions, are observed on irradiated surfaces. Similar phenomena occur in irradiated Ge surfaces (for example, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In 1988, Pearton et al 9) investigated production and removal of lattice damage in InAs, GaP and GaSb for implants of Si and Mg, and observed that zinc-blend type crystallites with a grain size of ∼ 17 nm remained on the implanted GaSb surface after annealing. In 1991, Callec et al 10) measured the elevations of the GaSb surface implanted under various conditions of ion species, acceleration voltage and ion doses and observed their cross-sectional views by scanning electron microscopy (SEM). They considered that the elevations occurred after amorphization since the critical dose for elevation was equal to that of amorphization.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Previous studies on ion implantation in GaSb have indicated swelling effects at the near-surface regions. 10 In the present investigation, we have carried out IM of p-GaSb by Ar ϩ ions and studied its effect on the electronic properties by the spatial resolved EBIC and cathodoluminescence ͑CL͒ techniques. EBIC measurements with metal on p-GaSb structures could not have been performed due to Fermi level pinning close to the valence band edge.…”
mentioning
confidence: 99%